Exploration of Mechanical Behaviors of Argillaceous Siltstone through Photoelastic Model Test and DEM Modelling - Weike Li; Jianqiang Han; Jie Cui; Weili Luo; Guangzao Zheng (Advances in Civil Engineering)
This paper aims at investigating mechanical behaviors of argillaceous siltstone through a photoelastic model test and DEM modelling. Both bonded and unbonded conditions were considered. The photoelastic model was fabricated in a controllable environment, and its scaled factor was 1 : 200 in length and 11.9 : 1 in Young’s modulus. The polariscope was designed to have an area-based LCD source and an automatic digital camera. A calibration test was carried out to obtain the relationship between the contact force and the average intensity gradient squared. A 2D DEM simulation is carried out for a 100 mm × 200 mm rectangular container filled with particles of 6 mm and 10 mm, in which the bonding effect is realized by adjusting the shear contact stiffness. The results show that both the photoelastic model and DEM modelling are able to capture the evolution of force chain network, effective contact number and stress concentration factor, and rheological behaviors when it is subjected to an increasing uniaxial load. The bonding effect plays an important role in the mechanical performance of argillaceous siltstone.